Etiology and epidemiology of playing-related musculoskeletal disorders – a systematic review - Zięba, Estera; Zieliński, Grzegorz; Ginszt, Michał (Journal of Education, Health and Sport, 2019)
Introduction: Instrumentalists are exposed to numerous musculoskeletal disorders (PRMD – Playing Related Musculoskeletal Disorders) or pain (PRP - Playing Related Pain). This condition is an effect of performance requirements, numerous rehearsals and stress. Musicians often underestimate the pain and the first symptoms of the overloads that their body sends them. They usually continue to practice for many hours a day, which only enlarges the damage of tissues. Unfortunately, this approach brings them closer to disability and exclusion from their profession. Aims: Overview of the latest research on concerting musicians. Gathering information on the etiology and epidemiology of PRMD and PRP among instrumentalists. Material and methods: This overview is based on studies from PubMed, ResearchGate and Google Scholar’s databases. In order to identify the relevant publications, the search was carried out using a combination of keywords: "musicians", "pain", "muscles". After applying the exclusion criteria, 16 assessed works were selected for the review. Results: The frequency of musculoskeletal disorders related to playing a musical instrument may reach 60%, up to over 80% [1,11,14,25,31-33]. The etiology of these dysfunctions should be associated with the repetitive movements of the upper limbs, either in uncomfortable positions assumed at work or in the specific posture of the body during the performance. One should also remember about the psychological aspect, which is important in understanding the mechanism of overloading and prolonged persistence of pain among musicians. An overview of the literature showed that musculoskeletal disorder concerned women more often than men. The group of instruments that were connected with more frequent occurrence of pain were violins/violas and wind instruments. The most frequently affected body areas were: neck, back, and upper limbs. The information shown above is able to speed up diagnostics as well as proper therapy for professional musicians, which will contribute to their faster recovery. It should also indicate the direction for future research on the prevention of the abovementioned disorders and the ergonomics of the musician profession. Conclusions: Professional musicians are a group particularly exposed to the occurrence of musculoskeletal disorders associated with playing an instrument, due to the specific requirements of their work. Looking at the high prevalence of these disorders, it can be concluded that the knowledge about the etiology and the prevention of overload and pain is small, and the instrumentalists themselves do not seek help from specialists. Further research in the above-discussed problem is essential to enhance prevention and ergonomics of musician profession.